1997
DOI: 10.1080/03601239709373113
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro effects of deltamethrin on cytochrome p450 monooxygenase activity in carp (cyprinus carpio L.) liver

Abstract: The in vivo and in vitro effects of the insecticide deltamethrin (DM) on hepatic cytochrome P450 (Cyt P450) monooxygenase were examined in adult carp. The in vivo experiments were carried out with 0.2 microgram/l DM at 20 degrees C. The changes in the hepatic microsomal Cyt P450 content and the Cyt P450-dependent monooxygenase activities were studied in DM-treated fish. Although there were no changes in the Cyt P450 content during the exposure time, after treatment for 24 h all the investigated isoenzyme activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…ECOD activities of microsomes from carp and trout were greater than carp homogenates (data in Dyer et al, 2008). The ECOD activity in trout was similar to that reported by Banka et al (1997).…”
Section: Subcellular Characterizationsupporting
confidence: 84%
“…ECOD activities of microsomes from carp and trout were greater than carp homogenates (data in Dyer et al, 2008). The ECOD activity in trout was similar to that reported by Banka et al (1997).…”
Section: Subcellular Characterizationsupporting
confidence: 84%
“…We found that the expression levels of CYP450 and glutathione metabolism genes were downregulated, which means that CYP450 and glutamathione are relevant to deltamethrin metabolism. Our results were consistent with those of previous studies: Banka et al [ 59 ] found that CYP450 enzymes were inhibited by deltamethrin in vivo and in vitro, and Abdel-Daim et al [ 60 ] revealed that deltamethrin could induce lipid peroxidation and glutathione reduction. However, Erdogan et al [ 61 ] found a significant increase in CYP450 in the muscle of rainbow trout exposed to deltamethrin, and Olsvik et al [ 62 ] reported that the levels of non-enzymatic antioxidant glutathione were increased in all the tissues exposed to deltamethrin.…”
Section: Discussionsupporting
confidence: 94%
“…However, cis-permethrin and fenpropathrin were reported to be inhibitors of CYP1A measured on rat liver microsomes in vitro [47]. Moreover, deltamethrin was found to inhibit several hepatic cytochrome P450 activities in a fish (Cyprinus carpio L.) at a concentration equal to 0.2 mg/L during 72-h exposure and fish-liver microsome (ECOD) activity [48]. Thus it cannot be excluded that the initial a-cypermethrininduced decrease in measured ECOD activity may be caused by inhibition, resulting in lower measurable activity.…”
Section: Sublethal Effects Of A-cypermethrinmentioning
confidence: 99%
“…Inhibition of cytochrome P450 activity caused by pyrethroids has not been extensively studied. Moreover, deltamethrin was found to inhibit several hepatic cytochrome P450 activities in a fish (Cyprinus carpio L.) at a concentration equal to 0.2 mg/L during 72-h exposure and fish-liver microsome (ECOD) activity [48]. Moreover, deltamethrin was found to inhibit several hepatic cytochrome P450 activities in a fish (Cyprinus carpio L.) at a concentration equal to 0.2 mg/L during 72-h exposure and fish-liver microsome (ECOD) activity [48].…”
Section: Sublethal Effects Of A-cypermethrinmentioning
confidence: 99%